Electric field computation analysis for the Electric Field Detector (EFD) on board the China Seismic-Electromagnetic Satellite (CSES). Issue 10 (15th November 2017) - Diego, P.; Bertello, I.; Candidi, M.; Mura, A.; Coco, I.; Vannaroni, G.; Ubertini, P.; Badoni, D.
Abstract: The floating potential variability of the Electric Field Detector (EFD) probes, on board the Chinese Seismo-Electromagnetic Satellite (CSES), has been modeled, and the effects of several structural and environmental elements have been determined. The expected floating potentials of the probes are computed considering the ambient ionospheric plasma parameter variations. In addition, the ion collection variability, due to the different probe attitudes along the orbit, and its effect on each floating potential, are considered. Particular attention is given to the analysis of the shadow produced by the stubs, in order to determine the artificial electric field introduced by instrumental effects which has to be subtracted from the real measurements. The modulation of the altered electric field, due to the effect on shadowing of the ion drift, as measured by the ESA satellite Swarm A in a similar orbit, is also modeled. Such simulations are made in preparation of real EFD data analysis performed during the upcoming flight of CSES.